2016
DOI: 10.1186/s13223-016-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Allergen inhalation challenge, refractoriness and the effects of ibuprofen

Abstract: BackgroundBronchoprovocation challenges use direct or indirect acting stimuli to induce airflow obstruction. Indirect stimuli either non-allergic/non-IgE mediated (e.g. exercise, mannitol) or allergic/IgE mediated (i.e. allergen) trigger mast cells to release bronchoconstricting mediators (e.g. cysteinyl leukotrienes, histamine). Performing repeat challenges within a short timeframe (e.g. 3 h) with non-allergic indirect stimuli results in a diminished, refractory response to the second challenge that is inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another large review of the literature (472 articles) demonstrated that not only is there a low risk of ibuprofen-induced asthma in children, but that the drug might have protective and therapeutic effects [ 61 ]. Interestingly, it was recently suggested that ibuprofen reduces the late response to specific bronchoprovocation with allergens and could, therefore, have a protective effect in allergen-induced asthma [ 62 ], but further evidence is required.…”
Section: Safety and Tolerability Of Ibuprofenmentioning
confidence: 99%
“…Another large review of the literature (472 articles) demonstrated that not only is there a low risk of ibuprofen-induced asthma in children, but that the drug might have protective and therapeutic effects [ 61 ]. Interestingly, it was recently suggested that ibuprofen reduces the late response to specific bronchoprovocation with allergens and could, therefore, have a protective effect in allergen-induced asthma [ 62 ], but further evidence is required.…”
Section: Safety and Tolerability Of Ibuprofenmentioning
confidence: 99%
“…Different from IgE-mediated allergy, which is mediated by cell-surface receptors, the drugs are able to induce mast cell degranulation and alter enzymatic activity through various pathways [34,35]. Cysteinyl LTs (cysLTs) and histamine, released by mast cells, mediate bronchoconstriction [36]. …”
Section: Mechanisms Of Pseudoallergymentioning
confidence: 99%
“…If we include early responders, we may be able to gain insight into allergen-induced increases in AHR since early responders show an increase at 3 hours post allergen challenge. 40 At 24 hours post challenge, early responders have also shown increased AHR, 41 as well as increased eosinophils and fractional exhaled nitric oxide, 42 but without developing a classic LAR. By using a method that incorporates both the classic dual and EAR models (i.e.…”
Section: Anothermentioning
confidence: 99%
“…31 Some studies have shown that the inclusion of participants who fell between 10-15% during the LAR time frame strengthened the data set, especially considering that these participants showed similar results to those who had met the current LAR criteria. 31,42 Future allergen challenge models could potentially reduce the cut-off point for defining the LAR to 10% without negatively influencing study outcomes.…”
Section: Referencesmentioning
confidence: 99%